Analysis of Λ0b → pK−μ+μ− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
The differential branching fraction and angular coefficients of $$ Λ_b^0 $$→ pK−μ+μ− decays are measured in bins of the dimuon mass squared and dihadron mass. The analysis is performed using a data set corresponding to 9 fb−1 of integrated luminosity collected with the LHCb detector between 2011 and 2018. The data are consistent with receiving contributions from a mixture of Λ resonances with different spin-parity quantum numbers. The angular coefficients show a pattern of vector-axial vector interference that is a characteristic of the type of flavour-changing neutral-current transition relevant for these decays.